The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1677/joe.0.1820249
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of prostaglandin production and agonist responsiveness by n-6 polyunsaturated fatty acids in endometrial cells from late-gestation ewes

Abstract: We investigated the effect of n-6 polyunsaturated fatty acids (PUFAs) on prostaglandin (PG) production by the uterus. A mixed population of endometrial cells (epthelium and stroma) from late-gestation ewes were cultured in defined medium containing linoleic acid (LA, 18:2, n-6), -linolenic acid (GLA, 18:3, or arachidonic acid (AA, 20:4, in concentrations of 0 (control), 20 or 100 µM. After 45 h in test medium with or without added PUFAs, cells were challenged with control medium (CM), oxytocin (OT, 250 nM), li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
2
15
1
Order By: Relevance
“…OA also increased PGE2 production in the fetal placenta. Our previous work has similarly demonstrated that supplementation of ME cells isolated from late gestation ewes with LA, conjugated LA, GLA and AA also increased the E:F ratios [28,38]. In contrast to our data, it was demonstrated that LPS induced an endocrine switch from PGF2α to PGE2 in bovine uterine endometrial cells [39].…”
Section: Discussioncontrasting
confidence: 99%
“…OA also increased PGE2 production in the fetal placenta. Our previous work has similarly demonstrated that supplementation of ME cells isolated from late gestation ewes with LA, conjugated LA, GLA and AA also increased the E:F ratios [28,38]. In contrast to our data, it was demonstrated that LPS induced an endocrine switch from PGF2α to PGE2 in bovine uterine endometrial cells [39].…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests the ability of bovine cumulus cells to metabolize LA and produce PGs. These results are in accordance with a previous study using endometrial cells of late gestation ewes, where the PGE 2 :PGF 2a ratio increased 2-3 times when cells were supplemented with the linoleic, g-linolenic or arachidonic acid (Cheng et al 2004). PGE is an autocrine/ paracrine mediator of oocyte maturation and cumulus expansion.…”
Section: Discussionsupporting
confidence: 92%
“…Medium was changed every 48-72 h. At the start of day 6, culture medium was replaced with DMEM/F-12, supplemented with 0.1125% fatty acid-free BSA and 0.1 ml/100 ml ITS media supplement, for a period of 3 h to remove any fatty acids present in the FCS (Cheng et al 2004). Cells were then cultured in the presence of 0, 20 or 100 mM n-6 PUFAs (LA, 18:2, n-6; GLA, 18:3, n-6; DGLA, 20:3, n-6 or AA, 20:4, n-6) or 0, 20 or 100 mM n-3 PUFAs (ALNA, 18:3, n-3; SA, 18:4, n-3; EPA, 20:5, n-3 and DHA, 22:6, n-3) for 45 h, as this time point was shown to be optimal for assessing PG generation following PUFA supplementation in the ovine amnion (Cheng et al 2003).…”
Section: Experimental Protocolmentioning
confidence: 99%